PERBANDINGAN KADAR AIR SERASAH MAHONI (Swietenia mahagoni) DAN ANGSANA (Pterocarpus indicus) TERHADAP PELUANG TERJADINYA KEBAKARAN HUTAN PADA MUSIM KEMARAU DI AREAL KHDTK MANDIANGIN - Yuwandi Arif Wardana; Normela Rachmawati; Susilawati Susilawati (Universitas Lambung Mangkurat, 2021)
Forest fires that occur in the dry season will also result in water content as well as plants. Plants often used during reclamation are Mahoni (Swietenia Mahagoni) and Angsana (Pterocarpus Indicus). The purpose of this research is to calculate the water content of mahoni and angsana litter in the dry season, determine the level of insecurity of both litter against the chances of forest fires occurring, and compare the water content of both litter in the dry season in the area of KHDTK Mandiangin. Sampling plots in the field using a plot 10 x 10 meters in purposive sampling is a deliberate and determined data retrieval of 15 replays on each type of plant. The plot is then made into a sub plot of 1 x 1 meter for the capture of a 200 gram plant. Samples of litter from the field are then tested for water content in the laboratory. The level of fire insecurity is determined by taking into account the percentage of litter water content. The comparison of both Litter Water content to the chance of forest fires in the dry season in KHDTK mandiangin area is the water content of Mahoni plants 14.96% and angsana plant litter water content is 15.02%. Both litter water content belongs to the category of fire prone because it is below the percentage value of 30%. According to the Follow-up T Test that has been conducted there is no significant difference in water content between Mahoni and Angsana plant.Musim kemarau yang berkepanjangan akan menyebabkan kadar air tanaman menjadi berkurang dan mudah menyebabkan kebakaran disuatu lahan. Tanaman yang sering digunakan pada saat reklamasi ialah tanaman Mahoni (Swietenia Mahagoni) dan Angsana (Pterocarpus Indicus). Tujuan dari penelitian ini adalah untuk menghitung kadar air serasah mahoni dan angsana pada musim kemarau, menentukan tingkat kerawanan serasah mahoni dan angsana terhadap peluang terjadinya kebakaran hutan, dan membandingkan kadar air serasah mahoni dan angsana pada musim kemarau di areal KHDTK (Kawasan Hutan Dengan Tujuan Khusus) Mandiangin. Pengambilan sampel plot di lapangan menggunakan plot 10 x 10 meter secara purposive sampling yaitu pengambilan data ditentukan sebanyak 15 kali ulangan pada masing-masing jenis tanaman. Plot dibuat menjadi sub plot 1 x 1 meter untuk pengambilan seresah tanaman seberat 200 gram. Sampel seresah diuji kadar airnya di laboratorium. Tingkat kerawanan api ditentukan dengan memperhitungkan persentase kadar air serasah. Perbandingan Kadar Air serasah mahoni dan angsana terhadap Peluang pada musim kemarau Terjadinya Kebakaran Hutan di areal KHDTK Mandiangin ialah kadar air serasah tanaman Mahoni 14,96% dan kadar air serasah tanaman Angsana yaitu 15,02%. Kadar air serasah Mahoni dan Angsana ini termasuk kategori rawan terhadap kebakaran karena berada dibawah nilai persentase 30%. Menurut Uji Lanjutan T yang telah dilakukan tidak ada perbedaan kadar air yang signifikan antara tanaman mahoni dan angsana